Incidencia e infestación de Hypsipyla grandella con control etológico en plantaciones establecidas de Cedrela odorata “cedro”. en Puerto Almendra, Loreto, Perú. 2022 - Yumbato Castro, Johan Sebastián (2024)
The limiting pest for cedar and mahogany cultivation in Latin America and the Caribbean is undoubtedly the moth Hypsipyla grandella. "shoot borer” Several control methods were applied, but the use of physical and ethological control using barriers and intelligent solar lights were not evaluated despite their good potential in the ethological control of agricultural pests. The objective of the project was to determine if ethological control (applying white and yellow artificial lights) decrease the incidence and infestation of Hypsipyla grandella in clonal gardens and plantations of Cedrela odorata "cedro". The study was developed in the Fundo Almendra of the Faculty of Forestry Sciences of the UNAP, which has a plantation of "cedar" with a high incidence of H. grandella, all the larvae of H. grandella were removed and fumigated throughout the plantation, then in two plots were installed 6 poles 4 m high with intelligent solar lights (white and yellow) that were turned on from 6 pm to 6am, in the control plot no lights were installed. The number of infested plants, the number of damaged shoots and the number of larvae/shoots were recorded biweekly for 10 months. The results indicate that the incidence of H. grandella was lower in the lights with respect to the control, which achieved 100% damage. In infestation, the groups exposed to white light and yellow light exhibited lower infestation and shoot damage compared to the control group. These results indicate that LED light acts as a repellent effect and reduces the presence of H. grandella in C. odorata plants, making it a promising technique for the control of this pest in the Peruvian Amazon.